2004
DOI: 10.1093/cercor/bhh115
|View full text |Cite
|
Sign up to set email alerts
|

Time Modulated Prefrontal and Parietal Activity during the Maintenance of Integrated Information as Revealed by Magnetoencephalography

Abstract: Using magnetoencephalography, we investigated the spatiotemporal patterns of brain magnetic activity responsible for maintaining verbal and spatial information in either an integrated or an unintegrated fashion. Considering time dimension, we noted a greater activation of a fronto-parietal network in early latencies during the maintenance of integrated information, and a different pattern during the maintenance of unintegrated material, showing a greater activation in a fronto-posterior network in late latenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 63 publications
4
22
1
1
Order By: Relevance
“…No such binding effect was expected when location was the relevant feature, however. Similar to the results obtained in previous neuroimaging studies of visual-feature binding (Donner et al, 2002;Shafritz et al, 2002;Todd and Marois, 2004;Vogel and Machizawa, 2004;Xu and Chun, 2006), findings from functional magnetic resonance imaging (fMRI) and MEG/EEG studies highlight prefrontal and parietal regions as the neuroanatomical correlates of verbal-spatial binding Campo et al, 2005;Prabhakaran et al, 2000;Wu et al, 2007). In essence, these previous studies provide haemodynamic or evoked electrical/ magnetic correlates of binding without addressing the physiological mechanisms underlying this process.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…No such binding effect was expected when location was the relevant feature, however. Similar to the results obtained in previous neuroimaging studies of visual-feature binding (Donner et al, 2002;Shafritz et al, 2002;Todd and Marois, 2004;Vogel and Machizawa, 2004;Xu and Chun, 2006), findings from functional magnetic resonance imaging (fMRI) and MEG/EEG studies highlight prefrontal and parietal regions as the neuroanatomical correlates of verbal-spatial binding Campo et al, 2005;Prabhakaran et al, 2000;Wu et al, 2007). In essence, these previous studies provide haemodynamic or evoked electrical/ magnetic correlates of binding without addressing the physiological mechanisms underlying this process.…”
supporting
confidence: 78%
“…As verbal-spatial binding was observed only in the verbal task it can be inferred that the greater oscillatory activity found in prefrontal areas might be signaling neural processes specifically involved in cross-code binding. However, it is important to highlight that the prefrontal activity in the current study was mainly observed in dorsal and medial regions corresponding to Brodmann's areas (BA) 9 and 46 (see also Campo et al, 2005), while in the study of Prabhakaran et al this activity was found in BA10. Whether this difference is related to specific mechanisms supporting implicit vs. explicit binding should explored in future studies.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations